2004
DOI: 10.1002/chp.1340240108
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge translation: The role and place of practice reflection

Abstract: Reflection is the mechanism by which we contemplate and try to understand relatively complex and sometimes troubling ideas for which there is no obvious solution. Reflection allows us to transform current ideas and experiences into new knowledge and action. Personal experiences and organizational feedback can trigger reflection, whereas a lack of time, available colleagues, and social networks detract from the ability professionals have to reflect. Educational programs can encourage reflection through the judi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 8 publications
0
49
0
1
Order By: Relevance
“…The IAT itself is inherently normative; results are provided in comparison to others. Consistent with published literature (Kember et al 1996;Lockyer et al 2004), group discussion often served as a secondary trigger for continued or additional reflection, through exposure to a diversity of beliefs and observations. When those beliefs or observations were offered in conjunction with comparison to personal standards, other students were sometimes motivated to consider their own personal standards.…”
Section: Discussionmentioning
confidence: 86%
“…The IAT itself is inherently normative; results are provided in comparison to others. Consistent with published literature (Kember et al 1996;Lockyer et al 2004), group discussion often served as a secondary trigger for continued or additional reflection, through exposure to a diversity of beliefs and observations. When those beliefs or observations were offered in conjunction with comparison to personal standards, other students were sometimes motivated to consider their own personal standards.…”
Section: Discussionmentioning
confidence: 86%
“…38 Reflection, as a form of mental processing, 39 allows physicians to make information and knowledge more meaningful. 40 Several studies have demonstrated that diaries~computerized or paper-and-pencil! assist physicians in recording and reflecting on their learning activities.…”
Section: Learning and Continuing Medical Educationmentioning
confidence: 99%
“…Although numerous theoretical contributions to the current understanding of reflection have been developed, [6][7][8][9][10][11][12] there are several challenges to using these models when considering how health professionals use reflection to implement learning from short courses into practice. First, most are based on student populations, student-teacher dyads, or learning through practice rather than short course learning.…”
Section: Introductionmentioning
confidence: 99%